Impact of Albendazole Therapy on Clinical and Radiological Outcomes at One Month in Patients with Active Solitary Neurocysticercosis Patients - Bhattarai, S.; Thapa, L.; Maharjan, A. M. S.; Shrestha, A. M.; Shrestha, S.; Ghimire, M. R.; Upadhyaya, S.; Thapa, M. (Kathmandu University Medical Journal, 2022)
Background Cerebral neurocysticerosis is a common parasitic disease of human nervous system but evidence on duration of albendazole therapy and their outcomes in this condition is inadequate Objective To evaluate the impact of varying duration of albendazole therapy on the clinical and radiological outcomes at one month in patients with active solitary neurocysticercosis. Method This is an interventional study conducted at Upendra Devkota Memorial National Institute of Neurological and Allied sciences, Bansbari over 1 year (2017 March - 2018 February). One hundred eighteen patients with new onset seizure secondary to active solitary cysticercal granuloma either received albendazole therapy for 1, 3, 9 or 21 days with the usual care or only received the usual care. Clinical and radiological outcomes were observed at one month follow-up. The difference in the proportion of the outcome measures between intervention and control groups were assessed using chi-square test. Result Our study included 118 patients with male predominance of 61.9%. Albendazole therapy for 3, 9 and 21 days reduced headache by 57.2%, 70.0% and 63.1% respectively which was higher than those with 1-day therapy or without the therapy. This difference in the proportion was statistically significant at p=0.001. Though seizure recurrence also declined but the difference was not significant (p=0.406) between groups. However, at one-month follow-up, majority of patients who received albendazole for 9 days (14, 70%) and 21 days (14, 73.7%) had normal lesion, while most calcified lesion (21, 67.7%) was observed in those who did not receive albendazole therapy. The difference between lesion among the groups was significant (p < 0.001). Conclusion Albendazole therapy in patients with active solitary neurocysticercosis for 9 days is as effective as 21 days and better than 3 days in headache control and lesion dissolution but seizure control could be achieved irrespective of the treatment.